PELATIHAN DAN PENDAMPINGAN PEMBUATAN ANEKA OLAHAN MAKANAN PENDAMPING ASI (MP-ASI) BERBAHAN PANGAN LOKAL KAYA NUTRISI - Septian Emma Dwi Jatmika Jatmika; Siti Kurnia Widi Hastuti2 (P3M Universitas Aisyiyah Surakarta, 2019)
This Community Service and Empowerment Program offers solutions to overcome problems encountered in Sedayu, especially the under-five health problems, such as the lack of knowledge about the provision of MP ASI according to World Health Organization (WHO) standards, the lack of utilization of quality local foods for MP-ASI and many the provision of instant breastfeeding by mothers in infants, the provision of MP-ASI is less appropriate with the duration, frequency, texture and variation according to age stage and the lack of attention of parents related to the growth of infants. The data shows that there are many toddlers in Sedayu who suffer from malnutrition and even malnutrition and stunting (short). The purpose of this community service is to improve the community's knowledge about the making of MP ASI by optimizing the existing local wisdom. The hope of this program can improve the knowledge, behavior and health status of children under five. The target of this program is the mother of the students from the students ofÂ TK ABA Argomulyo, TK ABA Sedayu and TK Tapen, Sedayu Subdistrict, Bantul who have under five children. Activities undertaken include training on the basic principles of MP-ASI, training on making and assisting various processed MP-ASI using quality local food. And held a mini gallery of processed products of various variations of ASI MP using quality local food to promote MP ASI products to the public.